SENI DALAM PANDANGAN ALQURAN - Yedi Purwanto (Jurnal Sosioteknologi, 2010)
The Qur'an is a holly book (kitabullah) revealed to Prophet Muhammad. One of al-qur'an functions is as a guide or guidance for mankind, which details God's other holly books. (Qur'an: 2:185). One form of al-qur'an guidance is about art. Al-qur'an globally discusses art, whether painting art, painting, and other arts. One of Allah"Ÿs natures is Al-Jamil (the most beautiful), and He loves beauty. Islam as Din (religion) which the Qur'an generated highly appreciate the arts, gave a stimulus for art work in accordance with the laws of Allah and the guidance of the Prophet SAW. Key words: Art and the Quran